Analysis of Hungarian programs for broadband infrastructure development - Gergely Kis (International Telecommunications Society (ITS), 2011)
In an effort to promote the information society, the Hungarian government adopted a number of strategic concepts and action plans, which formed the basis of many calls for proposals to be funded by the government and the European Union alike to achieve the institutional vision. In this article the author analyze in evaluating the government's role in Hungarian broadband infrastructure development programs so far. As a supposal in the course of the five government-funded infrastructure development programs implemented in Hungary by 2009, economic policymakers relegated community-based or community-owned digital telecommunication infrastructure to a heavily limited, stopgap role in terms of impact and extent. The basis of the investigation consisted of the RFPs for all of the five programs, as well as the data series showing the results of the projects already completed or yet to be finished under them. By analyzing them, it was possible to investigate the hypothesis.
Keywords: 330; broadband; government-funded infrastructure; development programs